Effects of temperature on the yields and properties of bio-oil from the fast pyrolysis of mallee bark - Mourant, Daniel; Lievens, Caroline; Gunawan, Richard; Wang, Yi; Hu, Xun; Wu, Liping; Syed-Hassan, Syed; Li, Chun-Zhu (Elsevier Ltd, 2013)
Bark constitutes an important part of any woody biomass to be used for the production of second generation biofuels and chemicals. Pyrolysis followed by biorefinery is a promising technology for the efficient utilisation of all components from a woody crop. While significant efforts have been devoted to the investigation of the pyrolysis characteristics of wood, relatively less is known about the pyrolysis behaviour of bark. This study aims to clarify the effects of temperature on the yields and composition of bio-oil from the pyrolysis of eucalypts bark. The bark of mallee, a type of eucalypt grown for soil amendment in Western Australia, was pyrolysed between 300 and 580 °C at fast heating rates in a fluidised-bed pyrolysis unit. The bio-oil liquid products separate into two phases. The bio-oil liquid products were analysed by GC–MS, Karl-Fischer titration, UV-fluorescence spectroscopy, ICP-OES and thermogravimetric analysis (TGA). These results are compared, when appropriate, to those obtained from the wood fraction.